Strategi Personal Branding Politik Kandidat Generasi Z dalam Membangun Keterpilihan pada Pemilu Legislatif Kota Jambi Tahun 2024 - Pungkas Sari Wismaningrum; Hatta Abdi Muhammad; M. Wira Anshori; Muliono Muliono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The phenomenon of Generation Z’s political electability in the 2024 Legislative Election reflects a shift in patterns of political representation at the local level. The success of Generation Z candidates in securing legislative seats in Jambi City has become a noteworthy phenomenon, particularly amid the dominance of politicians from older generations. This study aims to analyze the political personal branding strategies employed by Generation Z candidates in building their electability in the 2024 Legislative Election in Jambi City. The research adopts a qualitative approach, with data collected through interviews, documentation, and literature review. The analysis is based on Peter Montoya’s Personal Branding theory, which consists of specialization, Leadership, Personality, Distinctiveness, visibility, unity, persistence, and goodwill. The findings reveal that the electability of Generation Z candidates is influenced not only by their young age or social media presence but also by their ability to establish social closeness with the community, maintain consistency in political behavior, engage in intensive interpersonal communication, and actively participate in social and community activities. Personal branding strategies that are developed consistently and sustainably have proven effective in fostering public trust and strengthening political legitimacy at the local level. The study concludes that political personal branding is one of the key factors contributing to the electability of Generation Z candidates in the 2024 Legislative Election in Jambi City.